The research landscape of the quality of life or psychological impact on gynecological cancer patients: A bibliometric analysis - Zhao, Jiayuan; Kong, Yujia; Xiang, Yang; Yang, Junjun (Frontiers in Oncology, 2023)
Background: Gynecological cancer is one of the commonest cancers in women. The quality of life (QoL) or psychological impact has emerged as an outcome indicator in many clinical trials of gynecological cancer and gain a lot of concern in clinical when step into the 21st century. Our paper conducted a bibliometric analysis of QoL or psychological impact on gynecological cancer patients to show the status and hotspots. Methods: Related publications from 2000 to 2022 were included by screened from Web of Science Core Collection (WOSCC) on 26 June 2022. The bibliometrics was analyzed and visualized by bibliometrix R-package, VOSviewer and CiteSpace V. Results: 6479 publications were included in our study. The publications in this field were increased annually. United States (n=2075) is the country with most published papers. Sydney University (n=167) was the most productive affiliation. Gynecologic Oncology and Journal of Clinical Oncology were the most relevant and most cited sources, respectively. The article written by Bray F et al. has the highest citation. Kim J and Aaronson NK ranked the first in most productive author and most co-cited author, respectively. The keywords of ‘mortality’, ‘fertility preservation’ and ‘palliative care’ were still bursts till 2022, which represented the frontiers of this field. Conclusion: Our study provides an overall analysis in QoL or psychological impact on gynecological cancer patients, which can serve as a reference in the future research.